2020
DOI: 10.1021/acs.cgd.9b01476
|View full text |Cite
|
Sign up to set email alerts
|

ZnS–ZnO Heterostructure Nanorings Grown under a Possible Early Earth Atmosphere

Abstract: We synthesize ZnS–ZnO heterostructure nanorings at ∼680 °C under carrier gases with various [CO2]/[N2] ratios simulating an anoxic and weakly reduced atmosphere on early Earth. The synthesized nanorings consist of a ZnS–ZnO bilayered stem, ZnO teeth, and ZnS wing-like structures between the teeth and the ZnS layer. O atoms are supplied through the decomposition of CO2 presumably catalyzed by the ZnS surface. The respective growth directions of ZnS and ZnO layers in the stem are [0001] and [011̅1], and ZnO teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…ZnS and ZnO nanoparticles are also used as photocatalysts, both individually and together [184][185][186]. Apart from the potential of pure sulfide mineral semiconductors, it was also shown that mixed heterostructures based on ZnS and ZnO may be formed at high temperatures in an anoxic and weakly reduced atmosphere of the early Earth, and would possess a higher abiogenic photocatalytic activity in the CO2 reduction [187]. Pyrites [188,189] are another example of mineral structures with semiconductor and photocatalytic properties (including non-iron compounds -cattierite CoS2 [190,191], vaesit NiS2 [192,193] and others, often localized in paragenesis, in contact with autochthonous metals in the deposit [194,195]).…”
Section: Mineral Photosensitive Catalytic Semiconductors As the Basic...mentioning
confidence: 99%
“…ZnS and ZnO nanoparticles are also used as photocatalysts, both individually and together [184][185][186]. Apart from the potential of pure sulfide mineral semiconductors, it was also shown that mixed heterostructures based on ZnS and ZnO may be formed at high temperatures in an anoxic and weakly reduced atmosphere of the early Earth, and would possess a higher abiogenic photocatalytic activity in the CO2 reduction [187]. Pyrites [188,189] are another example of mineral structures with semiconductor and photocatalytic properties (including non-iron compounds -cattierite CoS2 [190,191], vaesit NiS2 [192,193] and others, often localized in paragenesis, in contact with autochthonous metals in the deposit [194,195]).…”
Section: Mineral Photosensitive Catalytic Semiconductors As the Basic...mentioning
confidence: 99%